Stereoselective Synthesis of Pyroglutamate Natural Product Analogs from α- Aminoacids and their Anti-Cancer Evaluation - Tekkam, Srinivas; A. Alam, Mohammad; J. Just, Matthew; M. Berry, Steven; L. Johnson, Joseph; C. Jonnalagadda, Subash; R. Mereddy, Venkatram (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Alkylation of α-amino acid derived iminoesters with Baylis-Hillman (BH) reaction template based allyl bromides/allyl acetates followed by acidic hydrolysis furnished α-methylene-β-substituted-pyroglutamates and α-alkylidene pyroglutamates respectively. Application of these methodologies has been demonstrated in the synthesis of fused [3.2.0]-γ-lactam-β-lactones. Further, substrate controlled stereoselective alkylation of L-threonine derived oxazoles with BH reaction based allyl bromides and acetates yielded optically pure α-methylene-β-substituted pyroglutamates, and α-alkylidene pyroglutamates. These methodologies have been applied in the preparation of chiral [3.2.0] heterobicyclic pyroglutamates containing hydroxyethyl side chain. All the synthesized pyroglutamates have been evaluated for their anti-cancer and enzyme proteasome inhibition activity.
Keywords: diastereoselective dihydroxylation